Association between number of children and carotid intima-media thickness in Bangladesh - Chat, Vylyny (PLoS One, 2018)
Previous studies on the association between number of children and carotid intima-media thickness (cIMT) were limited to Western populations. Pregnancy in women is associated with physiologic changes that may influence the risk of cardiovascular disease. Comparing the association between number of children and cIMT in men and women can provide insights on whether the association may be due to pregnancy. We investigated the association between number of children and cIMT among 718 female (mean age 37.5 years) and 417 male participants (mean age 41.3 years), randomly selected from the Health Effect of Arsenic Longitudinal Study (HEALS), a population-based cohort study in Bangladesh. Multivariate linear regression was used to assess the association and to control for education attainment, history of diabetes, age, smoking, betel use, BMI, systolic blood pressure, and diastolic blood pressure. The average number of children was 4.43 for women and 3.74 for men. There were no nulliparous women. We observed a positive association between number of children and cIMT in women. Mean cIMT increased by 4.5 μm (95% CI, 0.8–8.1) per increment of one birth (P = 0.02). Compared to women with two children, cIMT in women with 4 children and ≥5 children was 23.6μm (95%CI, 2.6–44.7; P = 0.03) and 25.1 μm (95%CI, 3.5–46.6; P = 0.02) greater, respectively. The association was not modified by BMI, SBP, betel use or age. Data in men showed no evidence of association (P = 0.4). The finding suggests a role of high parity in atherosclerosis in women of a low-income, high parity population.